High-temperature flexural strength performance of ternary high-entropy carbide consolidated via spark plasma sintering of TaC, ZrC and NbC. (15th April 2019) - Demirskyi, D.; Borodianska, H.; Suzuki, T.S.; Sakka, Y.; Yoshimi, K.; Vasylkiv, O.
Abstract: The solid solution formation and consolidation of the (Ta, Zr, Nb)C single-phase ceramic made from commercial TaC, ZrC and NbC powders prepared by spark plasma sintering at the temperature of 1920 °C was investigated. Phase analysis and lattice parameter measurements by X-ray diffraction showed multi-stage formation of the single-phase high-entropy-type carbide with the lattice parameter of 4.535 Å. The flexural strength and fracture toughness at room temperature were 460 ± 24 MPa and 2.9 MPa m 1/2, respectively. With an increase in temperature, the flexural strength showed an increase up to 1600 °C to 496 ± 44 MPa, then decreased after 1800 °C to 366 ± 46 MPa. Graphical abstract: Unlabelled Image